Finite element analysis of steel beams with web apertures under fire condiction - Kada, Abdelhak (2018)
This work is intended to analyse the behaviour steel beams with apertures under high temperatures rise due to fire using finite elements simulations with ANSYS software. It includes a structural fire analysis and a comparative study of cellular and castellated steel beams which takes into account transient temperature effect, material and geometric non-linear behaviour. FE models which estimate limiting time, mid-span deflection and failure temperature are presented for hexagonal and circular types of web opening shapes under several uniform load levels. The study shows that for any beam with closely spaced openings failure in fire will in most cases be caused by failure of the steel web. The numbers of web-openings and cells as well as their shapes are critical for the behaviour of castellated sections and cellular beams under fire condition.